INNOVATION DIFFUSION IN HEALTH SERVICES : EVALUATING INDONESIA’S PICK SICK GO HOME HEALTHY’ APPROACH - Novliza Eka Patrisia; Hardi Warsono; Kismartini Kismartini; Reni Shinta Dewi (Poltekkes Kemenkes Bengkulu, 2023)
This article aims to describe and qualitatively analyze the diffusion of healthcare service innovations in the